Physiological Response and Comprehensive Evaluation of Cold-Resistant Peach Varieties to Low-Temperature Stress - Ruxuan Niu; Juanjuan Huang; Yiwen Zhang; Falin Wang; Chenbing Wang (Agronomy)
The study aimed to evaluate the cold tolerance of various peach cultivars under diverse low-temperature conditions (−5, −10, −15, −20, −25, −30, and −35 °C). A comprehensive assessment of their responses to cold was performed by integrating LT50 values with membership functions and evaluating local adaptability among the selected peach cultivars. The findings revealed that as temperatures dropped, electrical conductivity (REC), malondialdehyde (MDA), and hydrogen peroxide (H2O2) levels initially rose, then fell, and subsequently increased once more. Soluble sugar (SS) and soluble protein (SP) concentrations peaked at −25 °C and showed a significant negative correlation with semi-lethal temperature (LT50). The expression of free proline varied among different samples. Combining physiological analyses with field adaptation correlation assessments, it was found that ‘Ziyan Ruiyang’ exhibited a relatively low LT50 value of −29.67 °C and a membership function degree of 0.76, suggesting robust field adaptation abilities. At the same time, ‘Ganlu Shumi’ demonstrated stable trends in H2O2 and MDA levels, maintaining them at relatively low concentrations; it also had the lowest LT50 value, the highest membership function score, and the highest survival rate. Consequently, this cultivar could be a valuable resource for enhancing cold resistance under low-temperature stress. In summary, by correlating LT50 values with membership functions and observing local adaptability in these peach cultivars, we have established reliable data that can serve as a basis for identifying potential cross-breeding parents to develop new cold-resistant varieties.